Teaching International Students to Analyze Textual-Discursive Categories - Ivanna Fetsko; Ilona Novak; Liubov Terletska; Oksana Soshko; Oksana Lytvynko (International Journal of Evaluation and Research in Education (IJERE), 2022)
The purpose of the study is to identify how the course that covers the components of the ten step-wise approach to discourse analysis of political texts helps international students study the political meanings in Ukraine. The study used the structured observation method to collect rather quantitative than qualitative data and observers’ reports on the sampled students’ performance in the in-class and out-of-class assignments. It also used discourse analysis awareness test, observation report checklist, and assessment checklist to yield the quantitative data. The course that is based on the ten-step-wise approach to discourse analysis of political texts proved to raise the students’ overall awareness of analysis of textual-discursive categories and fosters their skills of both discourse analysis and technical skills to use the NVivo 12 software tool. The results of the discourse analysis awareness test showed that the sampled students’ awareness of discourse analysis was generally good. The mean values varied between 0.643 and0.857 which corresponded to 65-85 grades ECTS. The analysis of the observation reports showed that the five most frequent words used in the corpus of the observation reports of seven experts were as follows:  students, contributed, equally, succeeded, managed. All of them evoke a positive idea and feeling and reveal success in meeting goals. The quotes yielded from the reports implied that the course sessions were engaging, challenging, and fruitful in terms of learning how to analyze textual-discursive categories found in political texts. The descriptive statistics drawn from the observation checklist and presented by course topic showed that the observers’ mean values improved throughout the course sessions that meant that the students progressed in the discourse analysis.